Reproducing the inherent variability of soils using a three-dimensional printer. Issue 6 (25th September 2020) - Pua, Lina-María; Caicedo, Bernardo
Abstract : This paper describes a new approach to modelling the three-dimensional (3D) variability of soil by using a multi-material 3D printer to extrude slurries of different types of clays. First, a distribution of the liquid limit in space was obtained using random field theory. Then, a 3D clay printer was developed to reproduce the complex patterns obtained analytically. The 3D clay printer can use eight types of homogeneous soils made from mixtures of kaolin, bentonite and colourant. The next step was fine-tuning of printing velocity and optimal water content for each type of clay. Consolidation involved two stages: use of a rigid plate to impose low stresses followed by use of a flexible membrane to control the stress rather than displacement during the consolidation process. The variability of the sample built-up with the 3D printer was assessed by measuring the undrained strength and electrical resistivity. Then the electrical resistivity was correlated with porosity. The results showed the differences between probability distributions of each soil's properties including liquid limits, electrical resistance, porosity and undrained shear strength. These differences are results of the consolidation process that tends to homogenise the sample and the failure mode of the experimental method used to evaluate the sample.